Pengaruh Program MBG terhadap Perubahan IMT/U (Indeks Massa Tubuh Menurut Umur) pada Siswa SMP Swasta Nahdlatul Ulama(NU) Medan - Adelia Safitri (Kampus Akademik Publiser, 2026)
The Free Nutritious Meal Program (MBG) is a government initiative designed to support students’ nutritional needs and improve their nutritional status. This study aimed to analyze changes in Body Mass Index-for-Age (BMI-for-Age) among students at Nahdlatul Ulama (NU) Junior High School Medan during the implementation of the MBG Program. This quantitative study employed an analytical observational design with a prospective cohort approach. The study population consisted of 56 eighth- and ninth-grade students, all of whom were selected using total sampling. Data were collected through measurements of body weight and height before and after the implementation of the MBG Program. BMI-for-Age was determined using Z-scores based on age and sex. Data were analyzed using univariate analysis, the Shapiro-Wilk normality test, and a paired sample t-test. The results showed that most students had normal nutritional status both before and after the program, accounting for 85.7%. The mean BMI-for-Age decreased from 1.154 to 1.096. However, the paired sample t-test showed a significance value of 0.765 (>0.05), indicating no statistically significant difference in BMI-for-Age before and after the MBG Program. Continuous evaluation of the program is needed, particularly regarding menu quality, food consumption, and implementation duration.